Value-oriented risk management of insurance companies - Kriele, Marcus (EAA Series, 2014)
Value- and risk-oriented management is a holistic method of managing businesses. In this book both actuarial methods and methods pertaining to classical internal control and classical risk management are used. Therefore the approach taken is necessarily interdisciplinary. Indeed, there is a new dynamically developing field for actuaries as a result of the emphasis now on the measurement of risk. This book provides the required basic knowledge for this subject from an actuarial perspective. It enables the reader to implement in practice a risk management system that is based on quantitative methods. With this book, the reader will additionally be able to critically appraise the applicability and the limits of the methods used in modern risk management. Value- Oriented Risk Management of Insurance Companies focuses on risk capital, capital allocation, performance measurement and value-oriented management. It also makes a connection to regulatory developments (for example, Solvency II). The reader should have a basic knowledge of probability and familiarity with mathematical concepts. It is intended for working actuaries and quantitative risk managers as well as actuarial students.